Straw and phosphorus applications promote maize (Zea mays L.) growth in saline soil through changing soil carbon and phosphorus fractions - Guo, Zhenxin; Ye, Wenhua; Wang, Hui; He, Wei; Tian, Yanling; Hu, Guoqing; Lou, Yanhong; Pan, Hong; Yang, Quangang; Zhuge, Yuping (Frontiers in Plant Science, 2024)
Introduction Straw return has been widely recognized as an important carbon (C) enhancement measure in agroecosystems, but the C-phosphorus (P) interactions and their effects on plants in saline soils are still unclear. Methods In this study, we investigated the effects of straw return and three P application levels, no P fertilizer (Non-P), a conventional application rate of P fertilizer (CP), and a high application rate of P fertilizer (HP), on maize growth and soil C and P fractions through a pot experiment. Results and discussion The results revealed that the dry matter weight of maize plant was no difference between the two straw return levels and was 15.36% higher under HP treatments than under Non-P treatments. Plant nutrient accumulations were enhanced by straw addition and increased with increasing P application rate. Straw application reduced the activities of peroxidase (POD), superoxide dismutase (SOD), catalase, and the content of malondialdehyde (MDA) in maize plants by 31.69%, 38.99%, 45.96% and 27.04%, respectively. P application decreased SOD, POD activities and MDA content in the absence of straw. The contents of easily oxidized organic carbon (EOC), particulate organic carbon (POC) and the ratio of POC/SOC in straw-added soils were 10.23%, 17.00% and 7.27% higher, respectively, than those in straw-absent soils. Compared with Non-P treatments, HP treatments led to an increase of 12.05%, 23.04% in EOC, POC contents respectively, while a decrease of 18.12% in the contribution of MAOC to the SOC pool. Straw return improved the P status of the saline soil by increasing soil available P (14.80%), organic P (35.91%) and Ca2-P contents (4.68%). The structural equation model showed that straw and P applications could promote maize growth (indicated by dry matter weight, P accumulation, antioxidant enzyme activity and MDA content) through improving soil C and P availabilities. Conclusion This study provides evidence that straw return together with adequate P supply in saline soil can promote crop nutrient accumulation, attenuate the oxidation damage on crop growth, and be beneficial for SOC turnover and soil P activation.